2018
DOI: 10.5296/ijsw.v5i2.13472
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Potential of Social Worker Involvement in Hospital Emergency Departments: A Practice-Based Scoping Review

Abstract: Background: Social worker input into hospital emergency department (ED) services would appear to be central to the provision of effective, durable and comprehensive services. Unfortunately, there are few literature overviews to summarise this potential. Methods:A practice-based scoping review was conducted to identify the role and potential of social worker involvement in emergency department settings. After initial screening, abstracts of 252 articles were read and screened, resulting in 37 articles, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For example, an English study suggested older people valued help negotiating the demands of attending hospital and would like help with accessing social services (McLeod, Bywaters, and Cooke 2003) which might be suggestive of a rights-based approach. In the same way, there is an extensive international literature on the role of social workers in Emergency Departments (Bell et al 2018) yet the UK literature here is now mainly extremely dated. The power of hospital social work might therefore lie in its system knowledge and influence rather than its challenge or advocacy.…”
Section: Professional Authority or Powermentioning
confidence: 99%
“…For example, an English study suggested older people valued help negotiating the demands of attending hospital and would like help with accessing social services (McLeod, Bywaters, and Cooke 2003) which might be suggestive of a rights-based approach. In the same way, there is an extensive international literature on the role of social workers in Emergency Departments (Bell et al 2018) yet the UK literature here is now mainly extremely dated. The power of hospital social work might therefore lie in its system knowledge and influence rather than its challenge or advocacy.…”
Section: Professional Authority or Powermentioning
confidence: 99%
“…At the pre-EMS stage, social workers act as cultural liaisons; 19 during the emergency, they act as crisis intervention with family and patients; 20 and the post-EMS services carried out by social workers include avoiding unnecessary hospitalizations, critical illness, and follow up. 21 This study aimed to synthesize the role of social work at three stages (pre-EMS, during emergency, and post-EMS emergency periods) globally. The role of social work for EMS is a well-known service all over the world, but the practice system is diverse, and community people are still unaware of the professional services of the social worker in EMS.…”
Section: Introductionmentioning
confidence: 99%
“…At the pre-EMS stage, social workers act as cultural liaisons; 19 during the emergency, they act as crisis intervention with family and patients; 20 and the post-EMS services carried out by social workers include avoiding unnecessary hospitalizations, critical illness, and follow up. 21 …”
Section: Introductionmentioning
confidence: 99%